Experimental Research on Internal Behaviors of Caved Rocks under the Uniaxial Confined Compression - Yu-jiang Zhang; Guo-rui Feng; Ting-ye Qi (Advances in Materials Science and Engineering, 2017)
As main composition of longwall gob, caved rocks’ behaviors and their impacts under compression crucially influence strata control, subsidence, associated resources extraction, and many other aspects. However, current researches are based on a whole sample, due to looseness of caved rocks and limitation of observation technology. In this paper, an experiment system was built to investigate internal behaviors of caved rocks’ sample, under the uniaxial confined compression, including movement and breakage behavior by the digital image processing technologies. The results show that the compression process of caved rocks could be divided into two stages by relative density. Boundary effect and changes of voids and contact pressure among caved rocks lead to different movement law in different position in sample’s interior. A stratification phenomenon of breakage was discovered, which presents breakage concentration in the middle of the sample. The nonlinear movement and shear dislocation induced by shifts among caved rocks are the reason of the breakage stratification phenomenon. This phenomenon would have an effect on the permeability and seepage research of similar medium.